2010
DOI: 10.1111/j.1365-2923.2009.03557.x
|View full text |Cite
|
Sign up to set email alerts
|

Peer teaching: a randomised controlled trial using student-teachers to teach musculoskeletal ultrasound

Abstract: Complicated technical skills can be adequately taught to students using the PAL system by STs with limited training. Self-teaching learning strategies are successful in contexts of limited teacher training. However, despite positive objective results, STs still face prejudice from students with regard to competency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
191
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(219 citation statements)
references
References 24 publications
13
191
1
7
Order By: Relevance
“…Contradicting the finding of a previous study [6], it was shown that subjective results of students correlate with this objective OSCE performance measures showing more unsatisfactory ratings under the PAL students. Significant gender differences were only seen in palpatory diagnostic competencies in the staff-led group and in the subjective evaluation data of the peer-led group.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Contradicting the finding of a previous study [6], it was shown that subjective results of students correlate with this objective OSCE performance measures showing more unsatisfactory ratings under the PAL students. Significant gender differences were only seen in palpatory diagnostic competencies in the staff-led group and in the subjective evaluation data of the peer-led group.…”
Section: Discussionsupporting
confidence: 62%
“…PAL strategies with a limited student-teacher training seem unable to take the place of traditional training for coordinative demanding motor skills through experienced physicians, in contrast to technically oriented procedures [6]. These results prove the theories of different authors, who postulated that an exclusive and comprehensive training of the student-teachers including didactic components is an absolute necessity for success [2,3,19,20].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…De meeste hiervan richtten zich op het trainen van medisch technische vaardigheden (skillslab) en zijn uitgevoerd in de eerste jaren van de opleiding. [6][7][8][9][10][11][12][13] Bij objectieve toetsing van deze vaardigheden (Objective Structured Clinical Examination; OSCE) werden in vergelijking tot studenten die door stafleden onderwezen werden, gelijke tot hogere resultaten gevonden bij studenten die onderwezen Near-peer teaching in het coschap Interne Geneeskunde: een gerandomiseerde cross-over trial N [2][3][4][5][6][7][8][9][10] werden in een near-peer setting. Bovendien werd dit onderwijs door studenten vaak positiever gewaardeerd.…”
Section: Inleidingunclassified